The Emergence of E-Opinion Leadership on Social Networks: An Unpdated Literature Review - Fatima Ezzahra, Khouiammi; Chakib, Hamadi (International Journal of Engineering and Technology, 2019)
The emergence of social networks was followed by the emergence of new sources of influence that are e-opinion leaders.Academic literature has focused on the concept's antecedents, its method of identification, and its role. This article presents the evolution of the concept from the offline context to the online context as well as the main works that studied its conceptualization and its identification. The divergence of the results leaves the managers perplexed and some theoretical questions always open.Â Â